On the small sample distribution of the R/S statistic - Harrison, Michael; Treacy, Glenn (Economic & Social Studies, 1997)
This paper gives an account of the RlS statistic and its known properties. It assesses the adequacy of the asymptotic distribution of the statistic in the case of samples of small and moderate size, and suggests an improved approximation based on the beta distribution. The results indicate that the proposed beta approximation is superior to the asymptotic distribution for practical purposes. Hence a new table of critical values is presented as an alternative to that of Lo (1991).
Keywords: R/S statistic; Quantitative methods; Sampling